2013
DOI: 10.1186/1471-2334-13-345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of sepsis, severe sepsis, and septic shock in a cohort of infected patients from ten Colombian hospitals

Abstract: BackgroundSepsis has several clinical stages, and mortality rates are different for each stage. Our goal was to establish the evolution and the determinants of the progression of clinical stages, from infection to septic shock, over the first week, as well as their relationship to 7-day and 28-day mortality.MethodsThis is a secondary analysis of a multicenter cohort of inpatients hospitalized in general wards or intensive care units (ICUs). The general estimating equations (GEE) model was used to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(48 reference statements)
0
8
0
1
Order By: Relevance
“…La comparación entre grupos se hizo para las variables continuas por medio de la prueba t de Student o U de Mann-Whitney, según la distribución de los datos y para las variables dicotómicas con la prueba de χ 2 . Con base en la literatura médica disponible y las investigaciones previas de nuestro grupo 30,[35][36][37] , se consideraron los siguientes factores como potencialmente relacionados con mortalidad: edad, sexo, puntajes SOFA y APACHE II, sitio de adquisición de la infección (comunidad versus hospital), clasificación de los hemocultivos (grampositivos, gramnegativos, polimicrobianos u hongos) y comorbilidades: trauma o cirugía durante los últimos 30 días, inmunosupresión (trasplante de órganos, uso crónico de corticosteroides, antecedente de neoplasia o infección por VIH/SIDA), insuficiencia renal crónica, insuficiencia cardiaca congestiva, diabetes mellitus, enfermedad pulmonar obstructiva crónica, cirrosis, drogadicción o alcoholismo. Las anteriores variables se analizaron por medio de un modelo de regresión logística múltiple con la mortalidad a los 28 días como variable dependiente.…”
Section: Análisis Estadísticounclassified
“…La comparación entre grupos se hizo para las variables continuas por medio de la prueba t de Student o U de Mann-Whitney, según la distribución de los datos y para las variables dicotómicas con la prueba de χ 2 . Con base en la literatura médica disponible y las investigaciones previas de nuestro grupo 30,[35][36][37] , se consideraron los siguientes factores como potencialmente relacionados con mortalidad: edad, sexo, puntajes SOFA y APACHE II, sitio de adquisición de la infección (comunidad versus hospital), clasificación de los hemocultivos (grampositivos, gramnegativos, polimicrobianos u hongos) y comorbilidades: trauma o cirugía durante los últimos 30 días, inmunosupresión (trasplante de órganos, uso crónico de corticosteroides, antecedente de neoplasia o infección por VIH/SIDA), insuficiencia renal crónica, insuficiencia cardiaca congestiva, diabetes mellitus, enfermedad pulmonar obstructiva crónica, cirrosis, drogadicción o alcoholismo. Las anteriores variables se analizaron por medio de un modelo de regresión logística múltiple con la mortalidad a los 28 días como variable dependiente.…”
Section: Análisis Estadísticounclassified
“…Our model may thus assist clinicians during initial resuscitation as well as in later decision-making or to estimate the added prognostic value of novel biomarkers. We are aware of only as single other study that uses time-varying covariables to estimate the risk of sepsis progression during the first week in patients treated for infection [11]. They concluded that intraabdominal and respiratory sources of infection, independently of SOFA and APACHE scores, increased the risk of progression to more severe stages of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Since not all patients with an infection will develop sepsis and only a minority will progress to severe sepsis requiring Intensive Care Unit (ICU) admission. [11][12][13][14][15] Further research should therefore focus on patient improvement, alongside deterioration, of patients presenting to the ED with an infection.…”
Section: Introductionmentioning
confidence: 99%